4x+2x-12=36

Simple and best practice solution for 4x+2x-12=36 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x+2x-12=36 equation:


Simplifying
4x + 2x + -12 = 36

Reorder the terms:
-12 + 4x + 2x = 36

Combine like terms: 4x + 2x = 6x
-12 + 6x = 36

Solving
-12 + 6x = 36

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '12' to each side of the equation.
-12 + 12 + 6x = 36 + 12

Combine like terms: -12 + 12 = 0
0 + 6x = 36 + 12
6x = 36 + 12

Combine like terms: 36 + 12 = 48
6x = 48

Divide each side by '6'.
x = 8

Simplifying
x = 8

See similar equations:

| 37.7=2*3.14r | | 4(x+2)=12-7(x+3) | | -5(m+7)=-(1-4m)-7m | | =-2x+5 | | (35x-35)/(25x-40) | | -6*x=30 | | 4sin(x/2) | | -6+x=30 | | 4x-8=-2(5x-13) | | 115+0.35p=65 | | 7(8c-1)-10=54+7 | | 5x^3+8x^2+7=0 | | 115=0.35+65 | | 1/3x9x5 | | 0.35p+65=115 | | 2.67p+3(.67p-8)=-10 | | 65+0.35p=115 | | 2.5x+58.9=0.9-9.1x | | 4e^13x=16 | | x^2-16+51=0 | | 3(2t+-5)+2t=30-t | | -1c=-7 | | 15=8x+13 | | 18x+21=21 | | 2x-19+19=85+19 | | 0.7(3x+6)=1-(x+3) | | 8+2x-4=9x+11-6x | | m=2-(-4)/-10-(-1) | | 900+7h=473.00 | | 548/x=109.6 | | 2740/x=548 | | 900+7h=473 |

Equations solver categories